Enhanced Sorption of Phenanthrene from Water by Modified Peat and the Thermodynamic Analysis - Zhou, Yanbo; Chen, Li; Lv, Wengang; Lu, Jun (Asian Journal of Chemistry, 2012)
In this study, the sorption processes of phenanthrene from aqueous solutions using natural and surfactant modified peat were investigated. The effects of initial concentration, contact time and temperature on the amount of phenanthrene adsorbed were studied and the mechanism involved was discussed. Good correlation coefficients were obtained for the pseudo-second-order kinetic model, showing that the sorption process of phenanthrene by peats followed the pseudosecond- order rate expression. The sorption capacity of peat increased with enhanced hydrophobicity and decreased surface negative charge. Equilibrium sorption studies showed that the sorption process was better described by the Langmuir isotherm in comparison to the Freundlich and Tempkin isotherm. The thermodynamic parameters were evaluated and the sorption of phenanthrene by peats was found to be spontaneous and exothermic. Evidently, modified peat has a great potential application in the effective remediation of polluted groundwater.